Trait rumination predicts onset of Post-Traumatic Stress Disorder through trauma-related cognitive appraisals: A 4-year longitudinal study. (August 2015) - Spinhoven, Philip; Penninx, Brenda W.; Krempeniou, Andriana; van Hemert, Albert M.; Elzinga, Bernet
Abstract: Trauma-related rumination and worry predict chronic PTSD. This study examined whether habitual rumination and worry measured prior to trauma exposure make persons more vulnerable to the onset of PTSD, presumably because habitual ruminators and worriers will be more prone to cognitively appraise trauma exposure in a negative way. A sample of 2981 adults aged 18–65, consisting of healthy controls and persons with past or current depressive and/or anxiety disorders were assessed at baseline and at follow-up four years later (n = 2402). At follow-up, 359 participants reported exposure to a traumatic event during the last four years of whom 52 (14.4%) had developed PTSD. Pre-trauma self-reported depression severity and trait rumination – but not trait worry-predicted onset of PTSD during follow-up, controlling for demographic and clinical history variables, as well as psychiatric diagnoses at baseline. The relation of trait rumination with onset of PTSD was partly mediated by the cognitive appraisal of the traumatic event and not by the affective reaction to trauma exposure. Repetitive negative thinking in the form of rumination may be a risk factor for onset of PTSD amenable to prevention and intervention. Highlights: Trauma-related rumination and worry are known to predict chronic PTSD. Pre-trauma trait rumination predicted onset of PTSD over and above other risk factors. Pre-trauma trait worry was not an independent risk factor for onset of PTSD. Cognitive appraisal of the trauma mediated the relation of trait rumination with PTSD.